Treatment adherence and BMI reduction are key predictors of HbA1c 1 year after diagnosis of childhood type 2 diabetes in the United Kingdom. Issue 8 (11th October 2018) - Candler, Toby P.; Mahmoud, Osama; Lynn, Richard M.; Majbar, Abdalmonen A.; Barrett, Timothy G.; Shield, Julian P. H.
Abstract : Background/Objective: Type 2 Diabetes (T2DM) is increasing in childhood especially among females and South‐Asians. Our objective was to report outcomes from a national cohort of children and adolescents with T2DM 1 year following diagnosis. Methods: Clinician reported, 1‐year follow‐up of a cohort of children (<17 years) diagnosed with T2DM reported through the British Paediatric Surveillance Unit (BPSU) (April 2015‐April 2016). Results: One hundred (94%) of 106 baseline cases were available for review. Of these, five were lost to follow up and one had a revised diagnosis. Mean age at follow up was 15.3 years. Median BMI standard deviation scores (SDS) was 2.81 with a decrease of 0.13 SDS over a year. HbA1c <48 mmol/mol (UK target) was achieved in 38.8%. logHbA1c was predicted by clinician reported compliance and attendance concerns ( β = 0.12, P = <0.0001) and change in body mass index (BMI) SDS at 1‐year ( β = 0.13, P =0.007). In over 50%, clinicians reported issues with compliance and attendance. Mean clinic attendance was 75%. Metformin was the most frequently used treatment at baseline (77%) and follow‐up (87%). Microalbuminuria prevalence at 1‐year was 16.4% compared to 4.2% at baseline and was associated with a higher HbA1c compared to those without microalbuminuria (60 vs 49 mmol/mol, P = 0.03). Conclusions: Adherence to treatment and a reduction in BMI appear key to better outcomes a year after T2DM diagnosis. Retention and clinic attendance are concerning. The prevalence of microalbuminuria has increased 4‐fold in the year following diagnosis and was associated with higher HbA1c.